The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/lary.30049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medicaid Expansion on Rhinologic Cancer Presentation, Treatment, and Outcomes

Abstract: Objective: The United States Patient Protection and Affordable Care Act allocated funds for states to expand Medicaid coverage. However, several states declined expansion. We aim to determine whether Medicaid expansion is associated with healthcare coverage, cancer stage at diagnosis, treatment, and survival among patients with rhinologic cancer. Rhinologic cancer was defined to include cancer of the nasal cavity, paranasal sinus, nasopharynx, or olfactory nerve.Study design: Cohort study. Methods: Patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…A total of 2830 studies were initially identified for screening, of which 50 were included in the review . Reasons for exclusion are depicted in the Figure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2830 studies were initially identified for screening, of which 50 were included in the review . Reasons for exclusion are depicted in the Figure.…”
Section: Resultsmentioning
confidence: 99%
“…The most studied HNC subsite was laryngeal cancer with 25 studies (50%), followed by oral cavity and oropharynx, each with 19 studies (38%). The most assessed outcome was advanced overall stage at presentation or diagnosis among 37 studies (74%) . Other options included advanced tumor size, advanced nodal disease, metastatic disease at presentation, and delayed diagnosis.…”
Section: Resultsmentioning
confidence: 99%